Feeding ecology of Assamese macaques (Macaca assamensis) troops in Kaligandaki and Budhigandaki River basins of central Nepal - Suvas CHANDRA Ghimire; LAXMAN KHANAL; MUKESH KUMAR CHALISE (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ghimire SC, Khanal L, Chalise MK. 2021. Feeding ecology of Assamese macaques (Macaca assamensis) troops in Kaligandaki and Budhigandaki River basins of central Nepal. Biodiversitas 22: 2625-2634. Seasonal fluctuations in the availability of key food resources impact the foraging behavior of animals. This study aimed to examine the seasonal variations in feeding time of Assamese macaques (Macaca assamensis) in the sub-tropical deciduous riverine forest environment of central Nepal. Two troops of Nepal population of Assamese macaques, a troop from Kaligandaki River Basin (KRBT) and the next from Budhigandaki River Basin (BRBT) were studied by focal animal sampling method. Data from systematic behavioral observations were analyzed with reference to that of the vegetation surveys. Assamese macaques invested more than two-fifths (>40%) of the diurnal time on feeding. The KRBT consumed 71 plant species and the BRBT relied on 69 food plants. Leaves, mature and young, constituted the most dominant food item followed by the fruits and seeds. The two study troops inhabiting highly similar habitats of food plants (Sorensen’s Similarity Index = 0.93) didn’t have a significant difference in the selection of food-plant parts. However, the remarkable temporal difference in feeding plant parts was observed in concordance with their seasonal availability. Young leaves, when available during the spring and pre-monsoon were the major food items. Contrastingly, mature leaves were the food items during the winter on which animals were forced to rely when young leaves were scarce. We conclude that food choice and time investment on the feeding of different plant parts differ depending on the availability of food in the area. Macaques living in comparable habitats with similar food plants have analogous food choices and time investments.